Implementing Knowledge Management To Increase Business Support Department Performance At PT Samafitro - Irvansyah Rachman; Jann Hidajat Tjakraatmadja (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
The research objectives are to define the key knowledge required to increase the NPS Score. To define the strategy of improvement in knowledge management for the Business Support Department Team to reach the targeted NPS Score. This research employs a qualitative approach to explore the implementation of knowledge management in enhancing the performance of the business support department at PT Samafitro. The research identified key knowledge required to improve the NPS Score, including updated standard procedures, structured training programs, integrated knowledge management (KM) systems, and enhanced employee awareness supported by technology. To achieve the targeted NPS Score, effective KM strategies were developed across four capability areas: Strategy, People, Process, and Content Management & Technology. These strategies include establishing dedicated KM teams, conducting competency mapping, integrating KM into project management, organizing regular knowledge-sharing sessions, and upgrading technological platforms. The findings demonstrate that a comprehensive and structured KM approach significantly enhances business performance and contributes to achieving higher customer satisfaction levels.